ANALISIS PERUBAHAN UPACARA ADAT BATAK TOBA DALAM UPACARA SUASANA SUKACITA DI KELURAHAN KULIM KECAMATAN TENAYAN RAYA KOTA PEKANBARU - Panggabean, Mosar Anggiat; Hambali, Hambali; Eddison, Ahmad (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2020)
Abstract: The purpose of this study is to analyze the Batak customary ceremony in the festive atmosphere of Pekanbaru City, Tenayan Raya District, Kulim Village and To find out what is the reason for the change in Batak customary ceremony in Pekanbaru City, Tenayan Raya District, Kulim District